Cloning, expression and purification of autolysin from methicillin-resistant Staphylococcus aureus: potency and challenge study in Balb/c mice. (February 2017) - Haghighat, Setareh; Siadat, Seyed Davar; Sorkhabadi, Seyed Mehdi Rezayat; Sepahi, Abbas Akhavan; Mahdavi, Mehdi
Highlights: Immunization with r-autolysin induced specific antibodies capable of effectively eliminating bacteria in kidney. Immunization with r-autolysin as a candidate vaccine increased protectivity in experimental challenge. Autolysin is a valuable target for the development of vaccine candidate against methicillin-resistant Staphylococcus aureus. Abstract: Staphylococcus aureus (MRSA) is an opportunistic pathogen which causes a variety of clinical diseases and leads to high rates of morbidity and mortality. Development of an effective vaccine appears to be a useful strategy to control the infection. Here, the internal region of atl was cloned into the pET24a plasmid and expressed in E. coli BL21 (DE3). Cloning of atl was confirmed by colony-PCR, enzymatic digestion and sequencing. Protein expressed in E coli, BL21 DE3 and was confirmed with SDS-PAGE and western blot analysis. Subsequently, BALB/c mice were injected subcutaneously three times with 20 μg of the recombinant autolysin. After Bleeding, autolysin-specific total IgG antibodies and isotypes were evaluated using ELISA. Opsonophagocytic killing assay was performed and experimental challenge was done by intraperitoneal injection with sub lethal doses of MRSA in mice and also survival rate was regularly monitored. Results showed that vaccinated mice could exhibit higher levels of autolysin-specific antibodies (P < 0.0001) with a predominant IgG1 response versus control group. Results from in vitro experiments indicated that S. aureus opsonized with immunized-mice sera displayed significantly increased phagocytic uptake and effective intracellular killing versus non-immunized mice. The number of viable bacteria in the kidney of immunized mice showed 1000 times less than the control mice; additionally, an increased survival rate was found after immunization with the candidate vaccine versus control group. Results from this study demonstrated that the autolysin is a valuable target for the development of immunotherapeutic strategies against S. aureus and candidate vaccines.